Dairy farms efficiency analysis before the quota system abolishment - Kovács , Krisztián (Applied Studies in Agribusiness and Commerce, 2014)
The abolishment of the dairy quota system in the EU is expected to increase competition across dairy farms in Europe. Assuming a common price for milk in the EU, only the most efficient farms will survive in the new environment. The main objective of the research is to compare dairy farms in Germany, The Netherlands and Hungary about their technical efficiency. In the first part of the research, the efficiency is measured by partial efficiency indexes using one dimensional efficiency measuring. In the second part, the Stochastic Frontier Analysis (SFA) have to be used to measure efficiency in a multidimensional space, using six inputs and two outputs. It appears from the results that the highest efficiency farms are in the Netherlands, and then Germany and Hungary follow thus, we get that the most efficient farms are in the Netherlands with 84% efficient. The German farms are 76% efficient. The Hungarian farms are 68% efficient. With respect the abolishment of the dairy quota system, our results suggest that the Dutch farms are the most efficient, thus probably they will increase their production after the quota system. But because the size of the country we cannot expect dramatic changes in the European Dairy market. The Germans farms efficiency is lower, but their efficiency is also lower, so we won’t expect high increase about the dairy supply. The Hungarian dairy sector is not so efficient like the Dutch, and the size of the sector has also small among the European countries, thus if they want to survive the quota system demolishing, they have to increase their technical efficiency.